2006
DOI: 10.1063/1.2169540
|View full text |Cite
|
Sign up to set email alerts
|

A survey of anisotropy measurement techniques and study of thickness effect on interfacial and volume anisotropies in Co∕Pt multilayer media

Abstract: A survey of various measurement techniques, including the rotation method, the hard-axis hysteresis loop, and the torque measurement, is presented using Co∕Pt multilayer recording media. It is found that for highly exchange-coupled samples, the results from the rotational method are consistent with those from the hard-axis hysteresis loop and torque measurements. Such anisotropy measurements are applied to determine the interfacial anisotropy in Co∕Pt multilayers (MLs) by studying a series of Co∕Pt ML samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 17 publications
2
17
0
2
Order By: Relevance
“…Surprisingly large PMA values, up to 1 to 2 erg/cm 2 , have been reported, which are comparable or even larger than the PMA observed at Co|Pt or Co|Pd interfaces. 24,25 This result is quite general and has been observed in both crystalline (MgO) and amorphous (AlOx) barriers, using both natural or plasma oxidation. 26,27 The PMA could be dramatically improved under annealing, 10,28,29 and x-ray photoemission spectroscopy has demonstrated that the PMA could be correlated without ambiguity with the presence of oxygen atoms at the interface.…”
Section: Introductionmentioning
confidence: 58%
“…Surprisingly large PMA values, up to 1 to 2 erg/cm 2 , have been reported, which are comparable or even larger than the PMA observed at Co|Pt or Co|Pd interfaces. 24,25 This result is quite general and has been observed in both crystalline (MgO) and amorphous (AlOx) barriers, using both natural or plasma oxidation. 26,27 The PMA could be dramatically improved under annealing, 10,28,29 and x-ray photoemission spectroscopy has demonstrated that the PMA could be correlated without ambiguity with the presence of oxygen atoms at the interface.…”
Section: Introductionmentioning
confidence: 58%
“…These loops were measured in two geometries: magnetic field is applied in the film plane and out of the film plane. From the area difference between the in‐plane and out‐of‐plane M – H hysteresis loops, the effective magnetic anisotropy, K eff , can be extracted . While an in‐plane easy‐axis of magnetization with K eff = (3.6 ± 0.4) × 10 6 ergs cm −3 is obtained for the as‐grown FePt film (A1 phase), which is given by shape anisotropy ( K S = 2 π MnormalS2 = (3.4 ± 0.4) × 10 6 ergs cm −3 ), an annealing time of 5 s is already sufficient to turn the easy‐axis of the magnetization into the out‐of‐plane direction.…”
Section: Resultsmentioning
confidence: 99%
“…The samples have a perpendicular anisotropy K with a value of 3.94ϫ 10 5 J / m 3 at room temperatures determined by the rotation method. 12 from which a grain size of 12 nm was estimated. Figure 2 shows a set of time-resolved measurements on the sample.…”
Section: Resultsmentioning
confidence: 99%